Topical intraocular pressure therapy effects on pregnancy - Mendez-Hernandez, Carmen (Dove Medical Press, 2012)
PURPOSE: To assess the course of intraocular pressure (IOP), visual field progression, and adverse effects of antiglaucoma medication used during pregnancy. METHODS: Thirteen eyes of eight patients with glaucoma were examined. Their clinical records were reviewed to compare IOP, number of medications, and visual field indices (VFI) before, during, and after pregnancy using a two-tailed paired t-test. RESULTS: In seven (87.5%) of the eight patients, no disease progression was observed. IOP (mmHg) remained stable (baseline 17.3 ± 3.6; first trimester 17.4 ± 5.2, P = 0.930; second trimester 18.1 ± 4.7, P = 0.519; third trimester 20.2 ± 8.7, P = 0.344; and postpartum 21.5 ± 7.6, P = 0.136). The mean number of glaucoma treatments fell from 1.7 ± 0.52 before pregnancy to 0.83 ± 0.75 (P = 0.04) in the second and third trimesters. In one patient, IOP increased during pregnancy and there was further visual field loss. In the only patient kept on fixed combination timolol–dorzolamide therapy throughout pregnancy, labor was induced because of delayed intrauterine growth. CONCLUSIONS: No changes in IOP and VFI were detected in most patients despite a reduction in the number of hypotensive agents required. Delayed intrauterine growth in one patient under fixed combination timolol–dorzolamide treatment was observed whereas no other adverse effects were detected.